CMC / UiO66-NH2 / MnO2 synergistically losslessly modified carbon cloth reinforced resin friction material as well as method and application thereof
By constructing a multi-level structure of CMC/UiO66-NH2/MnO2 on the surface of carbon fiber, combined with the dual effects of mechanical engagement and chemical coupling, the problem of insufficient interface bonding between carbon fiber and resin matrix in the prior art is solved, and the mechanical and friction wear properties of friction materials are significantly improved.
Patent Information
- Application Number
- CN202510077359.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-17
- Publication Date
- 2025-05-02
- Estimated Expiration
- 2045-01-17
AI Technical Summary
When the prior art, when modifying the carbon fiber surface to strengthen its interface bonding with the resin matrix, there are problems such as acidification treatment leading to reduced fiber strength, environmental pollution, poor physical blending dispersion, and weak interface bonding ability.
CMC/UiO66-NH2/MnO2 synergistic non-destructive modification technology is adopted to construct a multi-level structure on the surface of carbon fiber through solvent-thermal reaction, improve interface bonding, and further strengthen interface performance through the dual effects of mechanical meshing and chemical coupling.
The mechanical properties and friction wear properties of carbon cloth-enhanced resin-based friction materials have been significantly improved, the tensile strength has been increased by 51.9%-91.6%, and the wear rate has been reduced by 33.1%-65.9%, and the effect of simple process, low cost and excellent performance has been achieved.
Smart Images

Figure CN119913749A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of wet friction materials, and specifically relates to a CMC / UiO66-NH 2 / MnO 2 Synergistic non-destructive modified carbon cloth reinforced resin friction material and method and application. Background Art
[0002] In the field of modern industry and transportation, friction materials are key components in mechanical clutch and braking systems, and their performance is directly related to the safety, reliability and durability of the equipment. With the advancement of science and technology and the rapid development of high-end equipment manufacturing, the performance requirements for friction materials are becoming increasingly stringent. Friction materials are not only required to have a stable friction coefficient, good wear resistance, high strength and toughness, but also to have good elastic recovery, thermal stability, low thermal expansion coefficient and excellent chemical stability. The comprehensive improvement of these properties is crucial to ensure the stable operation of various types of transportation vehicles, such as automobiles, railway locomotives, and aerospace vehicles under complex working conditions. Fiber-reinforced resin-based friction materials, with their unique performance advantages, have become a research hotspot and development direction in the field of friction materials. In order to further improve the performance of fiber-reinforced resin-based friction materials, researchers are constantly exploring new reinforcement materials and modification technologies. Among them, carbon fiber is widely used in the reinforcement of resin-based friction materials due to its excellent properties such as high strength, high modulus, high temperature resistance, corrosion resistance and wear resistance. However, the interface bonding problem between carbon fiber and resin matrix has always been a key factor restricting the performance improvement of composite materials. Due to the smooth surface and strong chemical inertness of carbon fiber, it is difficult for carbon fiber to form an effective bond with the resin matrix, which makes it easy for fiber debonding and matrix peeling to occur under actual working conditions, thus limiting the wide application of carbon cloth reinforced resin-based friction materials. Therefore, surface modification of carbon fiber to improve the modulus difference between the fiber and resin phases, increase the roughness of the fiber, and thus improve the interface bonding between the fiber and the resin is the key to improving the various properties of carbon cloth reinforced resin-based friction materials.
[0003] The Chinese patent "A method for preparing electron beam irradiated carbon fiber reinforced modified polyaryletherketone" with publication number CN116903895A first acidifies the carbon fiber, and then grafts a mixed modifier of olefin coupling agent, crosslinking aid and polyoxyethylene ether surfactant on the surface of the carbon fiber by physical blending. However, the acidification treatment will cause problems such as reduced fiber strength, poor stability and environmental pollution, while physical blending has disadvantages such as poor dispersibility, weak interface bonding ability and limited performance improvement, all of which limit the improvement of composite material performance. The Chinese patent "A method for preparing COF grafted modified carbon cloth / resin-based friction material" with publication number CN114575158A. The invention uses concentrated nitric acid to pretreat the carbon fiber, and then uses hydrothermal reaction to grow COF material in situ on the carbon fiber, and uses the carbon fiber cloth loaded with COF as a reinforcement, which is applied in the field of wet friction materials.
[0004] Although the above modification methods have improved the interfacial bonding strength between carbon fiber and resin matrix to a certain extent, there are still many challenges and problems. First, although acid treatment can increase the activity of carbon fiber surface, it will damage the bulk strength of the fiber and reduce its mechanical properties. At the same time, the waste liquid generated during the acid treatment process may also pollute the environment. Secondly, the physical blending method has the problems of poor dispersibility and weak interface bonding ability, resulting in limited modification effect and difficulty in significantly improving the overall performance of the composite material. In addition, although the modification of a single component can improve the wettability of fiber and resin to a certain extent, the effect of multi-component synergistic modification is more significant. Multi-component synergistic modification of carbon fiber, with the help of the dual effects of mechanical meshing and chemical coupling, can significantly strengthen the interfacial bonding between carbon fiber and resin matrix, thereby more effectively improving the tribological properties of the material. However, how to achieve uniform distribution and firm bonding of multiple components on the surface of carbon fiber, and how to further strengthen the interfacial bonding through the dual effects of mechanical meshing and chemical coupling, are still the difficulties and hot spots in current research. Therefore, exploring a more efficient, environmentally friendly modification method that can effectively improve the interfacial bonding strength between carbon fiber and resin matrix is of great significance to promote the development of fiber-reinforced resin-based friction materials. Summary of the invention
[0005] In order to overcome the shortcomings of the prior art, the present invention aims to provide a CMC / UiO66-NH 2 / MnO 2 Collaborative non-destructive modification of carbon cloth reinforced resin friction materials, methods and applications are used to solve the technical problem of how to efficiently and environmentally modify the surface of carbon fiber to strengthen the interface bonding between carbon fiber and resin matrix, thereby improving the comprehensive performance of carbon cloth reinforced resin-based friction materials.
[0006] In order to achieve the above object, the present invention adopts the following technical solutions: The invention discloses a CMC / UiO66-NH 2 / MnO 2 The preparation method of the synergistic non-destructive modified carbon cloth reinforced resin friction material comprises the following steps: 1) First, the carbon fiber cloth is soaked in acetone and washed, then soaked in a carboxymethyl cellulose solution, washed, and dried to obtain a pretreated carbon fiber cloth; 2) dissolving diaminoterephthalic acid in N,N-dimethylformamide, adding zirconium chloride and ultrasonically treating, adding acetic acid dropwise, mixing and stirring evenly to obtain a mixed solution; 3) The carbon fiber pretreated in step 1) is placed in the mixed solution of step 2) for a solvothermal reaction. After the reaction is completed, it is washed with N, N-dimethylformamide and anhydrous ethanol for multiple times, and freeze-dried once to obtain CMC / UiO66-NH 2 Synergistically modified carbon fiber cloth; 4) CMC / UiO66-NH obtained in step 3) 2 Synergistically modified carbon fiber arranged on MnO 2 The solution was subjected to a secondary solvothermal reaction, and after the reaction was completed, CMC / UiO66-NH 2 / MnO 2 Synergistic non-destructive modified carbon fiber cloth; 5) CMC / UiO66-NH obtained in step 4) 2 / MnO 2 The synergistic non-destructive modified carbon fiber cloth was vacuum impregnated in a phenolic resin ethanol solution, dried, and then hot-pressed to obtain CMC / UiO66-NH 2 / MnO 2 Synergistic non-destructive modified carbon cloth reinforced resin friction material.
[0007] Preferably, in step 1), the carbon fiber cloth is soaked in acetone for 30-60 hours; the carboxymethyl cellulose solution is prepared by adding 0.6-1.2 g of carboxymethyl cellulose to every 600 g of deionized water; and the soaking conditions in the carboxymethyl cellulose solution are: soaking at 75-95° C. for 2-4 hours.
[0008] Preferably, the amount ratio of the pretreated carbon fiber cloth, diaminoterephthalic acid, N,N-dimethylformamide, zirconium chloride and acetic acid is (4-8) g: (0.108-0.216) g: (50-100) ml: (0.14-0.28) g: (2-10) ml; In step 2), the mixing and stirring speed is 600-1500 r / min.
[0009] Preferably, in step 3), the temperature of a solvothermal reaction is 100-140° C. and the time is 20-30 h.
[0010] Preferably, in step 4), MnO 2 The solution is prepared by adding 0.0316-0.0632 g MnO to 50-100 ml of deionized water. 2 Prepared.
[0011] Preferably, in step 4), the temperature of the secondary solvent thermal reaction is 100-140° C. and the time is 10-24 h.
[0012] Preferably, in step 5), the mass fraction of the phenolic resin ethanol solution is 20%-25%; the immersion pressure is 0.07-0.1 MPa, and the immersion time is 24-26 hours.
[0013] Preferably, in step 5), the temperature of hot pressing curing is 160-180° C., the pressure is 3-8 MPa, and the curing time is 6-12 min.
[0014] The present invention also discloses a CMC / UiO66-NH 2 / MnO 2 Synergistic non-destructive modified carbon cloth reinforced resin friction material, using the above CMC / UiO66-NH 2 / MnO 2 The preparation method of synergistic non-destructive modified carbon cloth reinforced resin friction material is prepared, CMC / UiO66-NH 2 / MnO 2 The tensile strength of the synergistic non-destructive modified carbon cloth reinforced resin friction material is 463.73-585.07MPa; the friction coefficient is 0.124-0.134; the wear rate is 3.69×10 -12 -7.24×10 -12 m 3 / (N·m).
[0015] The present invention also discloses the above-mentioned CMC / UiO66-NH 2 / MnO 2 CMC / UiO66-NH prepared by the preparation method of synergistic non-destructive modified carbon cloth reinforced resin friction material 2 / MnO 2 Application of synergistic nondestructive modified carbon cloth reinforced resin friction material in vehicle braking.
[0016] Compared with the prior art, the present invention has the following beneficial effects: The invention discloses a CMC / UiO66-NH 2 / MnO 2The preparation method of synergistic non-destructive modified carbon cloth reinforced resin friction material was constructed. 2 / MnO 2 The multi-level structure cooperates with the modified carbon fiber cloth and builds a rigid-flexible interface reinforcement structure with the resin matrix, which improves the interface performance and significantly improves the mechanical properties and friction and wear properties of the friction material. 2 / MnO 2 The multi-layer structure firstly coats the surface of the carbon fiber with a layer of film-like CMC without damaging the strength of the carbon fiber itself, and introduces oxygen-containing functional groups such as carboxyl hydroxyl groups on the surface of the carbon fiber, which is a good opportunity for the in-situ growth of UiO66-NH 2 The crystals provided nucleation sites, and then the UiO66-NH 2 layer, dense and uniform octahedral UiO66-NH 2 The crystal surface contains a large number of amino and hydroxyl groups, which can improve wettability and construct MnO 2 layer, a large amount of MnO 2 Nucleation sites appear in UiO66-NH 2 The defects of the crystal, MnO 2 Then it grows from the inside of the defect and finally forms CMC / UiO66-NH 2 / MnO 2 Multi-level structure. On the one hand, needle-shaped MnO 2 Embedded in the first two layers of coating, it forms a mechanical bond with the carbon fiber, and also facilitates the mechanical bond between the carbon fiber and the resin. On the other hand, MnO 2 The surface contains a large number of oxygen-containing functional groups such as hydroxyl groups. During the hot pressing process, the carbon fiber and the resin form a chemical bond, which improves the interface performance and thus significantly improves the mechanical properties and friction and wear properties of the friction material. The preparation method of the present invention has the advantages of simple process, low cost and excellent performance. 2 / MnO 2 The tensile strength of the synergistic non-destructive modified carbon cloth reinforced resin friction material increased by 51.9%-91.6%, and the wear rate decreased by 33.1%-65.9%.
[0017] Further, in step 1), the carbon fiber cloth is soaked in acetone for 30-60 hours; acetone soaking can effectively remove oil, impurities, etc. on the surface of the carbon fiber cloth, improve the purity and surface activity of the carbon fiber, and create good conditions for the subsequent coating of carboxymethyl cellulose (CMC). The soaking time is controlled at 30-60 hours, which can not only ensure the cleaning effect, but also avoid the damage to the strength of the carbon fiber body caused by soaking for too long. The carboxymethyl cellulose solution is prepared by adding 0.6-1.2g of carboxymethyl cellulose to every 600g of deionized water; the precise CMC solution ratio ensures the uniformity and thickness of the coating layer, and avoids the problem of uneven coating or too thick / thin coating layer caused by too high or too low concentration. This helps to form a stable CMC layer and provides a good foundation for subsequent steps. The soaking conditions in the carboxymethyl cellulose solution are: soaking at 75-95℃ for 2-4 hours. Reasonable soaking temperature and time can ensure that CMC is fully adsorbed on the surface of the carbon fiber to form a uniform and dense coating layer. This helps to introduce sufficient oxygen-containing functional groups such as carboxyl and hydroxyl groups into UiO66-NH 2 The in situ growth of crystals provides ample nucleation sites.
[0018] Furthermore, the amount ratio of the pretreated carbon fiber cloth, diaminoterephthalic acid, N,N-dimethylformamide, zirconium chloride and acetic acid is (4-8) g: (0.108-0.216) g: (50-100) ml: (0.14-0.28) g: (2-10) ml; acetic acid controls different UiO66-NH 2 The appearance of MnO with different densities is regrown 2 ; By optimizing the dosage ratio of each raw material, it is possible to ensure that UiO66-NH 2 Uniform growth and density of crystals while avoiding raw material waste and unnecessary side reactions.
[0019] Furthermore, in step 2), the mixing speed is 600-1500 r / min. Appropriate stirring speed can promote the full mixing and uniform dispersion of the raw materials and improve the UiO66-NH 2 The growth rate and uniformity of the crystal should be controlled. At the same time, excessive rotation speed should be avoided to avoid fiber damage or solution splashing.
[0020] Furthermore, in step 3), the temperature of a solvothermal reaction is 100-140°C and the time is 20-30h; suitable temperature and time conditions can promote the reaction of UiO66-NH 2 In-situ growth of crystals while avoiding excessively high temperatures that would cause destruction of the crystal structure or degradation of carbon fiber performance.
[0021] Furthermore, in step 4), MnO 2The solution is prepared by adding 0.0316-0.0632 g MnO to 50-100 ml of deionized water. 2 Prepared. Precise MnO 2 The solution ratio can ensure that MnO 2 The uniformity and thickness of the layer should avoid too thick or too thin MnO 2 The layer has an adverse effect on the material properties.
[0022] Furthermore, in step 4), the temperature of the secondary solvent thermal reaction is 100-140°C and the time is 10-24h; suitable secondary solvent thermal reaction conditions can promote the 2 In UiO66-NH 2 Growth at crystal defects to form stable MnO 2 At the same time, avoid excessively high temperatures or prolonged periods of time that may cause material performance degradation.
[0023] Furthermore, in step 5), the mass fraction of the phenolic resin ethanol solution is 20%-25%; the impregnation pressure is 0.07-0.1MPa, and the time is 24-26h. Appropriate phenolic resin concentration can ensure good impregnation and bonding between the resin matrix and the carbon fiber cloth, while avoiding excessive concentration that leads to excessive resin, incomplete curing or decreased material performance.
[0024] Furthermore, in step 5), the temperature of hot pressing curing is 160-180°C, the pressure is 3-8MPa, and the curing time is 6-12min. Reasonable hot pressing curing conditions can promote the complete curing of the resin matrix and improve the overall strength and heat resistance of the material. At the same time, appropriate pressure and curing time can ensure the close bonding between the resin and the carbon fiber cloth to form a stable interface structure.
[0025] The present invention also discloses a CMC / UiO66-NH 2 / MnO 2 The tensile strength of the synergistic non-destructive modified carbon cloth reinforced resin friction material is 463.73-585.07MPa, which is 51.9%-91.6% higher than that of the traditional carbon cloth reinforced resin friction material, which is a significant improvement. This is mainly due to the CMC / UiO66-NH 2 / MnO 2 The synergistic modification of the multi-level structure not only enhances the interfacial bonding between carbon fiber and resin matrix, but also 2 The mechanical meshing action further improves the overall strength of the material. The friction coefficient is 0.124-0.134, which is ideal for the vehicle braking system, ensuring sufficient braking force while avoiding excessive friction and increased wear. The wear rate is 3.69×10 -12-7.24×10 -12 m 3 / (N·m), which is 33.1%-65.9% lower than that of traditional materials, significantly improving the service life and reliability of the material.
[0026] The present invention also discloses the above CMC / UiO66-NH 2 / MnO 2 Application of synergistic non-destructive modified carbon cloth reinforced resin friction material in vehicle braking. Since the friction material has a stable friction coefficient and a low wear rate, it can respond quickly and generate a stable braking force when the vehicle brakes, thereby shortening the braking distance and improving the braking efficiency. At the same time, the stable friction performance reduces the vibration and noise during braking, improving driving safety and comfort. The low wear rate means that the brake material can maintain a longer effective thickness during use, reducing the frequency of replacement, thereby extending the service life of the entire brake system. This not only reduces the vehicle maintenance cost, but also reduces the safety hazards caused by brake system failures. The friction material prepared by the present invention has good thermal stability and wear resistance, and can adapt to high-speed, high-frequency braking and braking requirements in harsh environments, such as high temperature, humidity, etc. This makes the material have broad application prospects in the braking systems of various types of vehicles. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 CMC / UiO66-NH prepared by the present invention 2 / MnO 2 SEM photos of the synergistically nondestructive modified carbon fiber cloth, where (a) is the original carbon fiber cloth, (b), (c) and (d) are CMC / UiO66-NH prepared in Example 1, Example 2 and Example 3, respectively. 2 / MnO 2 Synergistic non-destructive modified carbon fiber cloth.
[0028] Figure 2 CMC / UiO66-NH prepared by the present invention 2 / MnO 2 Comparison of tensile strength of synergistic non-destructive modified carbon cloth reinforced resin friction materials, where C1 is unmodified carbon cloth reinforced resin-based friction material, C2, C3 and C4 are CMC / UiO66-NH prepared in Example 1, Example 2 and Example 3 respectively. 2 / MnO 2 Synergistic non-destructive modified carbon cloth reinforced resin friction material.
[0029] Figure 3 CMC / UiO66-NH prepared by the present invention 2 / MnO 2Comparison of continuous friction coefficients of synergistically non-destructive modified carbon cloth reinforced resin friction materials, where C1 is an unmodified carbon cloth reinforced resin-based friction material, C2, C3 and C4 are CMC / UiO66-NH prepared in Example 1, Example 2 and Example 3, respectively. 2 / MnO 2 Synergistic non-destructive modified carbon cloth reinforced resin friction material.
[0030] Figure 4 CMC / UiO66-NH prepared by the present invention 2 / MnO 2 Comparison of wear rates of synergistically non-destructive modified carbon cloth reinforced resin friction materials, where C1 is unmodified carbon cloth reinforced resin-based friction material, C2, C3 and C4 are CMC / UiO66-NH prepared in Example 1, Example 2 and Example 3, respectively. 2 / MnO 2 Synergistic non-destructive modified carbon cloth reinforced resin friction material. DETAILED DESCRIPTION
[0031] The technical solution of the present invention will be described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0032] In the present invention, unless otherwise specified, all the embodiments and preferred implementation methods mentioned herein can be combined with each other to form a new technical solution.
[0033] In the present invention, unless otherwise specified, all technical features and preferred features mentioned herein can be combined with each other to form a new technical solution.
[0034] In the present invention, unless otherwise specified, percentage (%) or part refers to the weight percentage or weight part relative to the composition.
[0035] In the present invention, unless otherwise specified, the components or preferred components involved can be combined with each other to form a new technical solution.
[0036] In the present invention, unless otherwise specified, the numerical range "a~b" represents an abbreviation of any real number combination between a and b, where a and b are real numbers. For example, the numerical range "6~22" means that all real numbers between "6~22" have been listed in this document, and "6~22" is just an abbreviation of these numerical combinations.
[0037] The “range” disclosed in the present invention is in the form of a lower limit and an upper limit, which can be one or more lower limits, and one or more upper limits, respectively.
[0038] In the present invention, the term "and / or" used herein refers to any combination and all possible combinations of one or more of the associated listed items, and includes these combinations.
[0039] In the present invention, unless otherwise specified, each reaction or operation step can be carried out sequentially or in accordance with the sequence. Preferably, the reaction method herein is carried out sequentially.
[0040] Unless otherwise specified, the professional and scientific terms used herein have the same meanings as those familiar to those skilled in the art. In addition, any method or material similar or equivalent to the described content may also be applied to the present invention.
[0041] The present invention provides a CMC / UiO66-NH 2 / MnO 2 The preparation method of the synergistic non-destructive modified carbon cloth reinforced resin friction material comprises the following steps: Step 1: Pre-treat the carbon fiber cloth by soaking and washing with acetone and deionized water at room temperature to remove the sizing agent and impurities on the surface; Step 2: soak the carbon fiber cloth obtained in step 1 in a carboxymethyl cellulose solution, wash it two to three times with deionized water, and then dry it for later use; Step 3: First, dissolve diaminoterephthalic acid in N, N-dimethylformamide to obtain a mixed solution A. Next, zirconium chloride is added to the mixed solution A and subjected to ultrasonic treatment to obtain a mixed solution B. Then, acetic acid is added dropwise to form a mixed solution C. Subsequently, the carbon fiber cloth obtained in step 2 is rolled up and placed vertically in a polytetrafluoroethylene reactor containing mixed solution C for a solvothermal reaction. After the reaction is completed, it is repeatedly filtered and washed with N, N-dimethylformamide and anhydrous ethanol, and finally freeze-dried once to obtain CMC / UiO66-NH 2 Synergistically modified carbon fiber cloth; Step 4: First, MnO 2 Dissolve in deionized water and mix with ultrasonic to obtain MnO 2 Solution, the CMC / UiO66-NH obtained in step 3 2 The modified carbon fiber cloth is sewn into a column with thread and then placed vertically in a container containing MnO 2 The solution was subjected to a secondary solvothermal reaction in a polytetrafluoroethylene liner. After the reaction, it was washed with deionized water several times and then freeze-dried to obtain CMC / UiO66-NH 2 / MnO 2 Synergistic non-destructive modified carbon fiber cloth; Step 5: CMC / UiO66-NH obtained in step 4 2 / MnO 2 The synergistic non-destructive modified carbon fiber cloth was vacuum impregnated in a phenolic resin ethanol solution, dried, and hot-pressed and cured in a vulcanizer to obtain CMC / UiO66-NH 2 / MnO 2 Synergistic non-destructive modified carbon cloth reinforced resin friction material.
[0042] Furthermore, in step 1, the method for pre-treating and removing the sizing agent and impurities on the surface is: soaking the carbon fiber cloth in an acetone solution at room temperature for 30-60 hours.
[0043] Furthermore, in step 2, 0.6-1.2 g of carboxymethyl cellulose is added to every 600 g of deionized water. The conditions for soaking in the carboxymethyl cellulose solution are: soaking at 75-95° C. for 2-4 hours.
[0044] Furthermore, in step three, 4-8 g of carbon fiber cloth, 0.108-0.216 g of diaminoterephthalic acid and 0.14-0.28 g of zirconium chloride are added to every 50-100 ml of N,N-dimethylformamide.
[0045] Furthermore, in step 3, the magnetic stirring of the mixed liquid C is controlled to have a rotation speed of 600-1500 r / min, and 2-10 ml of acetic acid is added dropwise to the mixed liquid using a syringe.
[0046] Furthermore, in step three, the temperature of a solvothermal reaction is 100-140° C., and the time is 20-30 h.
[0047] Further, in step 4, MnO 2 The solution is prepared by adding 0.0316-0.0632 g MnO to 50-100 ml of deionized water. 2 .
[0048] Furthermore, in step 4, the temperature of the secondary solvent thermal reaction is 100-140° C., and the time is 10-24 h.
[0049] Furthermore, in step five, the mass fraction of the phenolic resin ethanol solution is 20%-25%; the immersion pressure is 0.07-0.1 MPa, and the time is 24-26 hours.
[0050] Furthermore, in step five, the process parameters of hot pressing curing in the vulcanizer are: temperature of 160-180° C., pressure of 3-8 MPa, and curing time of 6-12 min.
[0051] CMC / UiO66-NH disclosed in the present invention 2 / MnO 2The tensile strength of the synergistic non-destructive modified carbon cloth reinforced resin friction material is 463.73-585.07MPa, showing extremely strong load-bearing capacity and tensile resistance; the friction coefficient is 0.124-0.134, ensuring the stability and reliability during braking; the wear rate is 3.69×10 -12 -7.24×10 -12 m 3 / (N·m), showing excellent wear resistance and long service life. These excellent performance indicators make this material have broad application prospects and huge market potential in the field of high-performance friction materials.
[0052] CMC / UiO66-NH disclosed in the present invention 2 / MnO 2 The application of synergistic non-destructive modified carbon cloth reinforced resin friction material in vehicle braking. Its stable friction coefficient and extremely low wear rate can ensure the rapid response of vehicle braking and reliability under long-term use, providing strong material support for improving vehicle braking efficiency and safety.
[0053] In order to make the purpose, technical solutions and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, rather than all of the embodiments. The components of the embodiments of the present invention described and shown in the drawings here can usually be arranged and designed in various different configurations. Therefore, the following detailed description of the embodiments of the present invention provided in the drawings is not intended to limit the scope of the claimed invention, but merely represents selected embodiments of the present invention. Based on the embodiments in the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0054] Example 1 A CMC / UiO66-NH 2 / MnO 2 The preparation method of the synergistic non-destructive modified carbon cloth reinforced resin friction material comprises the following steps: Step 1: Put 6g of carbon fiber cloth into acetone, seal it and soak it at room temperature for 45h, then wash the carbon fiber cloth with deionized water for two to three times and dry it to obtain the pretreated carbon fiber cloth; Step 2: soak the pretreated carbon fiber cloth obtained in step 1 in a 0.15% carboxymethyl cellulose solution, treat it at 80° C. for 3 hours, wash it with deionized water two to three times, and then dry it for later use; Step 3: At room temperature, 0.108 g of diaminoterephthalic acid was dissolved in 50 mL of N,N-dimethylformamide to obtain a mixed solution A, and the mixed solution was subjected to ultrasonic treatment to uniformly disperse the diaminoterephthalic acid in the mixed solution A; Step 4: adding 0.14 g of zirconium chloride to the mixed solution A and then performing ultrasonic treatment to obtain a mixed solution B; Step 5: Add 2 mL of acetic acid dropwise to the mixed solution B, stir with a magnetic stirrer at a speed of 900 r / min, and mix well to obtain a mixed solution C; Step 6: Inject the mixed solution C and the carbon fiber cloth into a 100 mL polytetrafluoroethylene liner, and then fix the liner in a matching stainless steel reactor; Step 7: Fix the stainless steel reactor containing the mixed solution C and the carbon fiber cloth in a homogeneous reactor and react for 24 hours at 120°C and a rotation speed of 60 r / min to obtain the grafted UiO66-NH 2 Carbon fiber cloth; Step 8: Graft UiO66-NH obtained in step 7 2 The carbon fiber cloth was washed with N, N-dimethylformamide and anhydrous ethanol several times to remove the unreacted monomers and the UiO66-NH 2 and placed in an oven for drying; Step 9: Add 0.0316g MnO 2 Dissolve in 50 ml of deionized water, mix by ultrasonication to obtain solution D, and wash and dry the grafted UiO66-NH 2 The carbon fiber cloth is sewn into a column shape with thread and then placed vertically into a polytetrafluoroethylene liner, which is then fixed in a matching stainless steel reactor; Step 10: Fix the stainless steel reactor containing solution D and carbon fiber cloth in a homogeneous reactor and react for 12 hours at 100°C and a rotation speed of 50 r / min to obtain grafted MnO 2 Carbon fiber cloth; Step 11: Graft MnO obtained in step 10 2 The carbon fiber cloth was washed with deionized water several times to remove the unreacted monomers and the MnO that was not grafted on the carbon fiber cloth. 2 After freeze drying, CMC / UiO66-NH 2 / MnO 2 Synergistic non-destructive modification of carbon fiber cloth; CMC / UiO66-NH 2 / MnO 2The synergistic non-destructive modified carbon fiber cloth was vacuum impregnated in a phenolic resin ethanol solution with a mass fraction of 25%. The impregnation conditions were: pressure of 0.08 MPa at room temperature and impregnation time of 24 h. The preform after impregnation was placed in an oven and allowed to stand for drying, and then hot-pressed and cured with a vulcanizer. The hot-pressing curing conditions were: temperature of 175 ° C, pressure of 4 MPa, and curing time of 12 min to obtain CMC / UiO66-NH 2 / MnO 2 Synergistic non-destructive modified carbon cloth reinforced resin friction material.
[0055] The CMC / UiO66-NH prepared in Example 1 2 / MnO 2 The tensile strength of the synergistic non-destructive modified carbon cloth reinforced resin friction material is 491.73MPa; the friction coefficient is 0.124; and the wear rate is 5.4×10 -12 m 3 / (N·m).
[0056] Example 2 A CMC / UiO66-NH 2 / MnO 2 The preparation method of the synergistic non-destructive modified carbon cloth reinforced resin friction material comprises the following steps: Step 1: Put 6g of carbon fiber cloth into acetone, seal it and soak it at room temperature for 45h, then wash the carbon fiber cloth with deionized water for two to three times and dry it to obtain the pretreated carbon fiber cloth; Step 2: soak the pretreated carbon fiber cloth obtained in step 1 in a 0.15% carboxymethyl cellulose solution, treat it at 80° C. for 3 hours, wash it with deionized water two to three times, and then dry it for later use; Step 3: At room temperature, 0.108 g of diaminoterephthalic acid was dissolved in 50 mL of N,N-dimethylformamide to obtain a mixed solution A, and the mixed solution was subjected to ultrasonic treatment to uniformly disperse the diaminoterephthalic acid in the mixed solution A; Step 4: adding 0.14 g of zirconium chloride to the mixed solution A and then performing ultrasonic treatment to obtain a mixed solution B; Step 5: Add 6 mL of acetic acid dropwise to the mixed solution B, stir with a magnetic stirrer at a speed of 900 r / min, and mix well to obtain a mixed solution C; Step 6: Inject the mixed solution C and the carbon fiber cloth into a 100 mL polytetrafluoroethylene liner, and then fix the liner in a matching stainless steel reactor; Step 7: Fix the stainless steel reactor containing the mixed solution C and the carbon fiber cloth in a homogeneous reactor and react for 24 hours at 120°C and a rotation speed of 60 r / min to obtain the grafted UiO66-NH 2 Carbon fiber cloth; Step 8: Graft UiO66-NH obtained in step 7 2 The carbon fiber cloth was washed with N, N-dimethylformamide and anhydrous ethanol several times to remove the unreacted monomers and the UiO66-NH 2 and placed in an oven for drying; Step 9: Add 0.0316g MnO 2 Dissolve in 50 ml of deionized water, mix by ultrasonication to obtain solution D, and wash and dry the grafted UiO66-NH 2 The carbon fiber cloth is sewn into a column shape with thread and then placed vertically into a polytetrafluoroethylene liner, which is then fixed in a matching stainless steel reactor; Step 10: Fix the stainless steel reactor containing solution D and carbon fiber cloth in a homogeneous reactor and react for 12 hours at 100°C and a rotation speed of 50 r / min to obtain grafted MnO 2 Carbon fiber cloth; Step 11: Graft MnO obtained in step 10 2 The carbon fiber cloth was washed with deionized water several times to remove the unreacted monomers and the MnO that was not grafted on the carbon fiber cloth. 2 After freeze drying, CMC / UiO66-NH 2 / MnO 2 Synergistic non-destructive modification of carbon fiber cloth; CMC / UiO66-NH 2 / MnO 2 The synergistic non-destructive modified carbon fiber cloth was vacuum impregnated in a phenolic resin ethanol solution with a mass fraction of 25%. The impregnation conditions were: pressure of 0.08 MPa at room temperature and impregnation time of 24 h. The preform after impregnation was placed in an oven and allowed to stand for drying, and then hot-pressed and cured with a vulcanizer. The hot-pressing curing conditions were: temperature of 175 ° C, pressure of 4 MPa, and curing time of 12 min to obtain CMC / UiO66-NH 2 / MnO 2 Synergistic non-destructive modified carbon cloth reinforced resin friction material.
[0057] The CMC / UiO66-NH prepared in Example 2 2 / MnO 2 The tensile strength of the synergistic non-destructive modified carbon cloth reinforced resin friction material is 585.07MPa; the friction coefficient is 0.134; and the wear rate is 3.69×10 -12 m 3 / (N·m).
[0058] Example 3 A CMC / UiO66-NH 2 / MnO 2The preparation method of the synergistic non-destructive modified carbon cloth reinforced resin friction material comprises the following steps: Step 1: Put 6g of carbon fiber cloth into acetone, seal it and soak it at room temperature for 45h, then wash the carbon fiber cloth with deionized water for two to three times and dry it to obtain the pretreated carbon fiber cloth; Step 2: soak the pretreated carbon fiber cloth obtained in step 1 in a 0.15% carboxymethyl cellulose solution, treat it at 80° C. for 3 hours, wash it with deionized water two to three times, and then dry it for later use; Step 3: At room temperature, 0.108 g of diaminoterephthalic acid was dissolved in 50 mL of N,N-dimethylformamide to obtain a mixed solution A, and the mixed solution was subjected to ultrasonic treatment to uniformly disperse the diaminoterephthalic acid in the mixed solution A; Step 4: adding 0.14 g of zirconium chloride to the mixed solution A and then performing ultrasonic treatment to obtain a mixed solution B; Step 5: Add 10 mL of acetic acid dropwise to the mixed solution B, stir with a magnetic stirrer at a speed of 900 r / min, and mix well to obtain a mixed solution C; Step 6: Inject the mixed solution C and the carbon fiber cloth into a 100 mL polytetrafluoroethylene liner, and then fix the liner in a matching stainless steel reactor; Step 7: Fix the stainless steel reactor containing the mixed solution C and the carbon fiber cloth in a homogeneous reactor and react for 24 hours at 120°C and a rotation speed of 60 r / min to obtain the grafted UiO66-NH 2 Carbon fiber cloth; Step 8: Graft UiO66-NH obtained in step 7 2 The carbon fiber cloth was washed with N, N-dimethylformamide and anhydrous ethanol several times to remove the unreacted monomers and the UiO66-NH 2 and placed in an oven for drying; Step 9: Add 0.0316g MnO 2 Dissolve in 50 ml of deionized water, mix by ultrasonication to obtain solution D, and wash and dry the grafted UiO66-NH 2 The carbon fiber cloth is sewn into a column shape with thread and then placed vertically into a polytetrafluoroethylene liner, which is then fixed in a matching stainless steel reactor; Step 10: Fix the stainless steel reactor containing solution D and carbon fiber cloth in a homogeneous reactor and react for 12 hours at 100°C and a rotation speed of 50 r / min to obtain grafted MnO 2 Carbon fiber cloth; Step 11: Graft MnO obtained in step 10 2The carbon fiber cloth was washed with deionized water several times to remove the unreacted monomers and the MnO that was not grafted on the carbon fiber cloth. 2 After freeze drying, CMC / UiO66-NH 2 / MnO 2 Synergistic non-destructive modification of carbon fiber cloth; CMC / UiO66-NH 2 / MnO 2 The synergistic non-destructive modified carbon fiber cloth was vacuum impregnated in a phenolic resin ethanol solution with a mass fraction of 25%. The impregnation conditions were: pressure of 0.08 MPa at room temperature and impregnation time of 24 h. The preform after impregnation was placed in an oven and allowed to stand for drying, and then hot-pressed and cured with a vulcanizer. The hot-pressing curing conditions were: temperature of 175 ° C, pressure of 4 MPa, and curing time of 12 min to obtain CMC / UiO66-NH 2 / MnO 2 Synergistic non-destructive modified carbon cloth reinforced resin friction material.
[0059] The CMC / UiO66-NH prepared in Example 3 2 / MnO 2 The tensile strength of the synergistic non-destructive modified carbon cloth reinforced resin friction material is 463.73MPa; the friction coefficient is 0.126; and the wear rate is 7.24×10 -12 m 3 / (N·m).
[0060] Example 4 A CMC / UiO66-NH 2 / MnO 2 The preparation method of the synergistic non-destructive modified carbon cloth reinforced resin friction material comprises the following steps: Step 1: Put 4g of carbon fiber cloth into acetone, seal it and soak it at room temperature for 30 hours, then wash the carbon fiber cloth with deionized water two to three times and dry it to obtain the pretreated carbon fiber cloth; Step 2: soak the pretreated carbon fiber cloth obtained in step 1 in a 0.1% carboxymethyl cellulose solution, treat it at 75° C. for 2 hours, wash it with deionized water two to three times, and then dry it for later use; Step 3: At room temperature, 0.216 g of diaminoterephthalic acid was dissolved in 100 mL of N,N-dimethylformamide to obtain a mixed solution A, and the mixed solution was subjected to ultrasonic treatment to uniformly disperse the diaminoterephthalic acid in the mixed solution A; Step 4: adding 0.28 g of zirconium chloride to the mixed solution A and then performing ultrasonic treatment to obtain a mixed solution B; Step 5: Add 8 mL of acetic acid dropwise to the mixed solution B, stir with a magnetic stirrer at a speed of 600 r / min, and mix well to obtain a mixed solution C; Step 6: Inject the mixed solution C and the carbon fiber cloth into a 100 mL polytetrafluoroethylene liner, and then fix the liner in a matching stainless steel reactor; Step 7: Fix the stainless steel reactor containing the mixed solution C and the carbon fiber cloth in a homogeneous reactor and react for 20 hours at 100°C and a rotation speed of 60 r / min to obtain the grafted UiO66-NH 2 Carbon fiber cloth; Step 8: Graft UiO66-NH obtained in step 7 2 The carbon fiber cloth was washed with N, N-dimethylformamide and anhydrous ethanol several times to remove the unreacted monomers and the UiO66-NH 2 and placed in an oven for drying; Step 9: Add 0.0632g MnO 2 Dissolve in 100 ml of deionized water, mix by ultrasonication to obtain solution D, and wash and dry the grafted UiO66-NH 2 The carbon fiber cloth is sewn into a column shape with thread and then placed vertically into a polytetrafluoroethylene liner, which is then fixed in a matching stainless steel reactor; Step 10: Fix the stainless steel reactor containing solution D and carbon fiber cloth in a homogeneous reactor and react for 10 hours at 120°C and a rotation speed of 50 r / min to obtain grafted MnO 2 Carbon fiber cloth; Step 11: Graft MnO obtained in step 10 2 The carbon fiber cloth was washed with deionized water several times to remove the unreacted monomers and the MnO that was not grafted on the carbon fiber cloth. 2 After freeze drying, CMC / UiO66-NH 2 / MnO 2 Synergistic non-destructive modification of carbon fiber cloth; CMC / UiO66-NH 2 / MnO 2 The synergistic non-destructive modified carbon fiber cloth was vacuum impregnated in a phenolic resin ethanol solution with a mass fraction of 20%. The impregnation conditions were: pressure of 0.07 MPa at room temperature and impregnation time of 24 h. The impregnated preform was placed in an oven and allowed to stand for drying, and then hot-pressed and cured with a vulcanizer. The hot-pressing curing conditions were: temperature of 160 ° C, pressure of 4 MPa, and curing time of 6 min to obtain CMC / UiO66-NH 2 / MnO 2 Synergistic non-destructive modified carbon cloth reinforced resin friction material.
[0061] The CMC / UiO66-NH prepared in Example 4 2 / MnO 2The tensile strength of the synergistic non-destructive modified carbon cloth reinforced resin friction material is 555.34MPa; the friction coefficient is 0.125; and the wear rate is 4.26×10 -12 m 3 / (N·m).
[0062] Example 5 A CMC / UiO66-NH 2 / MnO 2 The preparation method of the synergistic non-destructive modified carbon cloth reinforced resin friction material comprises the following steps: Step 1: Put 8g of carbon fiber cloth into acetone, seal it and soak it at room temperature for 48 hours, then wash the carbon fiber cloth with deionized water two to three times and dry it to obtain the pretreated carbon fiber cloth; Step 2: soak the pretreated carbon fiber cloth obtained in step 1 in a 0.15% carboxymethyl cellulose solution, treat it at 95° C. for 4 hours, wash it with deionized water two to three times, and then dry it for later use; Step 3: At room temperature, 0.216 g of diaminoterephthalic acid was dissolved in 100 mL of N,N-dimethylformamide to obtain a mixed solution A, and the mixed solution was subjected to ultrasonic treatment to uniformly disperse the diaminoterephthalic acid in the mixed solution A; Step 4: adding 0.28 g of zirconium chloride to the mixed solution A and then performing ultrasonic treatment to obtain a mixed solution B; Step 5: Add 2 mL of acetic acid dropwise to the mixed solution B, stir with a magnetic stirrer at a speed of 700 r / min, and mix well to obtain a mixed solution C; Step 6: Inject the mixed solution C and the carbon fiber cloth into a 100 mL polytetrafluoroethylene liner, and then fix the liner in a matching stainless steel reactor; Step 7: Fix the stainless steel reactor containing the mixed solution C and the carbon fiber cloth in a homogeneous reactor and react for 20 min at 140°C and 60 r / min to obtain the grafted UiO66-NH 2 Carbon fiber cloth; Step 8: Graft UiO66-NH obtained in step 7 2 The carbon fiber cloth was washed with N, N-dimethylformamide and anhydrous ethanol several times to remove the unreacted monomers and the UiO66-NH 2 and placed in an oven for drying; Step 9: Add 0.0632g MnO 2 Dissolve in 100 ml of deionized water, mix by ultrasonication to obtain solution D, and wash and dry the grafted UiO66-NH 2The carbon fiber cloth is sewn into a column shape with thread and then placed vertically into a polytetrafluoroethylene liner, which is then fixed in a matching stainless steel reactor; Step 10: Fix the stainless steel reactor containing solution D and carbon fiber cloth in a homogeneous reactor and react for 10 hours at 120°C and a rotation speed of 50 r / min to obtain grafted MnO 2 Carbon fiber cloth; Step 11: Graft MnO obtained in step 10 2 The carbon fiber cloth was washed with deionized water several times to remove the unreacted monomers and the MnO that was not grafted on the carbon fiber cloth. 2 After freeze drying, CMC / UiO66-NH 2 / MnO 2 Synergistic non-destructive modification of carbon fiber cloth; CMC / UiO66-NH 2 / MnO 2 The synergistic non-destructive modified carbon fiber cloth was vacuum impregnated in a phenolic resin ethanol solution with a mass fraction of 22%. The impregnation conditions were: pressure of 0.09 MPa at room temperature and impregnation time of 25 h. The impregnated preform was placed in an oven and allowed to stand for drying, and then hot-pressed and cured with a vulcanizer. The hot-pressing curing conditions were: temperature of 180 ° C, pressure of 3 MPa, and curing time of 8 min to obtain CMC / UiO66-NH 2 / MnO 2 Synergistic non-destructive modified carbon cloth reinforced resin friction material.
[0063] The CMC / UiO66-NH prepared in Example 5 2 / MnO 2 The tensile strength of the synergistic non-destructive modified carbon cloth reinforced resin friction material is 482.54MPa; the friction coefficient is 0.132; and the wear rate is 4.31×10 -12 m 3 / (N·m).
[0064] Example 6 A CMC / UiO66-NH 2 / MnO 2 The preparation method of the synergistic non-destructive modified carbon cloth reinforced resin friction material comprises the following steps: Step 1: Put 7g of carbon fiber cloth into acetone, seal it and soak it at room temperature for 60 hours, then wash the carbon fiber cloth with deionized water two to three times and dry it to obtain the pretreated carbon fiber cloth; Step 2: soak the pretreated carbon fiber cloth obtained in step 1 in a 0.2% carboxymethyl cellulose solution, treat it at 95° C. for 4 hours, wash it with deionized water two to three times, and then dry it for later use; Step 3: At room temperature, 0.111 g of diaminoterephthalic acid was dissolved in 80 mL of N,N-dimethylformamide to obtain a mixed solution A, and the mixed solution was subjected to ultrasonic treatment to uniformly disperse the diaminoterephthalic acid in the mixed solution A; Step 4: adding 0.14 g of zirconium chloride to the mixed solution A and then performing ultrasonic treatment to obtain a mixed solution B; Step 5: Add 10 mL of acetic acid dropwise to the mixed solution B, stir with a magnetic stirrer at a speed of 1500 r / min, and mix well to obtain a mixed solution C; Step 6: Inject the mixed solution C and the carbon fiber cloth into a 100 mL polytetrafluoroethylene liner, and then fix the liner in a matching stainless steel reactor; Step 7: Fix the stainless steel reactor containing the mixed solution C and the carbon fiber cloth in a homogeneous reactor and react for 30 hours at 120°C and a rotation speed of 60 r / min to obtain grafted UiO66-NH 2 Carbon fiber cloth; Step 8: Graft UiO66-NH obtained in step 7 2 The carbon fiber cloth was washed with N, N-dimethylformamide and anhydrous ethanol several times to remove the unreacted monomers and the UiO66-NH 2 and placed in an oven for drying; Step 9: Add 0.0542g MnO 2 Dissolve in 50 ml of deionized water, mix by ultrasonication to obtain solution D, and wash and dry the grafted UiO66-NH 2 The carbon fiber cloth is sewn into a column shape with thread and then placed vertically into a polytetrafluoroethylene liner, which is then fixed in a matching stainless steel reactor; Step 10: Fix the stainless steel reactor containing solution D and carbon fiber cloth in a homogeneous reactor and react for 24 hours at 140°C and a rotation speed of 50 r / min to obtain grafted MnO 2 Carbon fiber cloth; Step 11: Graft MnO obtained in step 10 2 The carbon fiber cloth was washed with deionized water several times to remove the unreacted monomers and the MnO that was not grafted on the carbon fiber cloth. 2 After freeze drying, CMC / UiO66-NH 2 / MnO 2 Synergistic non-destructive modification of carbon fiber cloth; CMC / UiO66-NH 2 / MnO 2The synergistic non-destructive modified carbon fiber cloth was vacuum impregnated in a phenolic resin ethanol solution with a mass fraction of 25%. The impregnation conditions were: pressure of 0.1 MPa at room temperature and impregnation time of 26 h. The impregnated preform was placed in an oven and allowed to dry, and then hot-pressed and cured with a vulcanizer. The hot-pressing curing conditions were: temperature of 180 ° C, pressure of 8 MPa, and curing time of 12 min to obtain CMC / UiO66-NH 2 / MnO 2 Synergistic non-destructive modified carbon cloth reinforced resin friction material.
[0065] The CMC / UiO66-NH prepared in Example 6 2 / MnO 2 The tensile strength of the synergistic non-destructive modified carbon cloth reinforced resin friction material is 495.51MPa; the friction coefficient is 0.127; and the wear rate is 6.85×10 -12 m 3 / (N·m).
[0066] Comparative Example 1 A method for preparing an unmodified carbon cloth reinforced resin-based friction material comprises the following steps: Step 1: Soak 6g of carbon fiber cloth in acetone at room temperature for 45 hours to remove surface sizing and impurities, wash it repeatedly with deionized water three to four times and then dry it for use; Step 2: Vacuum impregnate the carbon fiber cloth obtained in step 1 into a phenolic resin ethanol solution with a mass fraction of 25%, and the impregnation conditions are: pressure of 0.08 MPa at room temperature and impregnation time of 24 h; Step 3: The impregnated preform is placed in an oven and allowed to dry, and then hot-pressed and cured in a vulcanizer to obtain an unmodified carbon cloth reinforced resin-based friction material. The hot-pressing curing conditions are: temperature 175° C., pressure 4 MPa, and curing time 12 min.
[0067] The unmodified carbon cloth reinforced resin-based friction material prepared in this comparative example 1 has a tensile strength of 305.33 MPa; a friction coefficient of 0.097; and a wear rate of 10.83×10 -12 m 3 / (N·m).
[0068] See also Figure 1 CMC / UiO66-NH prepared by the present invention 2 / MnO 2 SEM photos of the synergistically nondestructive modified carbon fiber cloth, where (a) is the original carbon fiber cloth, (b), (c) and (d) are CMC / UiO66-NH prepared in Example 1, Example 2 and Example 3, respectively. 2 / MnO 2Synergistic non-destructive modification of carbon fiber cloth; As can be seen from the figure, the original carbon fiber surface is smooth, and narrow and shallow grooves can be seen along the axial direction of the fiber. After modification, it can be seen that the surface of the carbon fiber is covered with needle-shaped MnO 2 .
[0069] Figure 2 CMC / UiO66-NH prepared by the present invention 2 / MnO 2 Comparison of tensile strength of synergistic non-destructive modified carbon cloth reinforced resin friction materials, where C1 is unmodified carbon cloth reinforced resin-based friction material, C2, C3 and C4 are CMC / UiO66-NH prepared in Example 1, Example 2 and Example 3 respectively. 2 / MnO 2 Synergistic non-destructive modified carbon cloth reinforced resin friction material; as can be seen from the figure, the tensile strength of the modified composite material is improved.
[0070] Figure 3 CMC / UiO66-NH prepared by the present invention 2 / MnO 2 Comparison of continuous friction coefficients of synergistically non-destructive modified carbon cloth reinforced resin friction materials, where C1 is an unmodified carbon cloth reinforced resin-based friction material, C2, C3 and C4 are CMC / UiO66-NH prepared in Example 1, Example 2 and Example 3, respectively. 2 / MnO 2 Synergistic non-destructive modified carbon cloth reinforced resin friction material; as can be seen from the figure, the friction coefficient of the modified composite material is improved.
[0071] Figure 4 CMC / UiO66-NH prepared by the present invention 2 / MnO 2 Comparison of wear rates of synergistically non-destructive modified carbon cloth reinforced resin friction materials, where C1 is unmodified carbon cloth reinforced resin-based friction material, C2, C3 and C4 are CMC / UiO66-NH prepared in Example 1, Example 2 and Example 3, respectively. 2 / MnO 2 Synergistic non-destructive modified carbon cloth reinforced resin friction material; as can be seen from the figure, the wear rate of the modified composite material is reduced.
[0072] In summary, the present invention discloses a CMC / UiO66-NH 2 / MnO 2 The preparation method of the synergistic non-destructive modified carbon cloth reinforced resin friction material comprises the following steps: firstly, the carbon fiber is immersed in a carboxymethyl cellulose solution, and a highly adhesive CMC film is coated on its surface to form a protective layer; then, a solvent thermal method is used to in situ grow dense and uniform octahedral UiO66-NH2 Grains; further grafted with UiO66-NH 2 In situ growth of needle-shaped nano-MnO on carbon fiber cloth with crystal grains by solvothermal method 2 . Constructed CMC / UiO66-NH 2 / MnO 2 The multi-level structure improves the interface performance of carbon fiber cloth / resin, significantly improves the mechanical and friction and wear properties of the friction material, and increases the friction coefficient from 0.097 to 0.134, an increase of 38.1%, and the wear rate from 10.83×10 -12 m 3 / (N·m) decreased to 3.69×10 -12 m 3 / (N·m), the wear rate decreased by 65.9%, and the tensile strength increased from 305.33MPa to 585.07MPa, with a tensile strength increase of 91.6%. It is expected to bring new breakthroughs and progress to the development of vehicle braking systems.
[0073] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A method for preparing a CMC / UiO66-NH2 / MnO2 synergistically non-destructive modified carbon cloth reinforced resin friction material, characterized in that: The following steps are involved: 1) First, the carbon fiber cloth is soaked in acetone and washed, then soaked in a carboxymethyl cellulose solution, washed, and dried to obtain a pretreated carbon fiber cloth; 2) dissolving diaminoterephthalic acid in N,N-dimethylformamide, adding zirconium chloride and ultrasonically treating, adding acetic acid dropwise, mixing and stirring evenly to obtain a mixed solution; 3) placing the carbon fiber pretreated in step 1) in the mixed solution of step 2) to carry out a solvothermal reaction, and after the reaction, washing with N, N-dimethylformamide and anhydrous ethanol for multiple times, and freeze-drying once to obtain CMC / UiO66-NH2 synergistically modified carbon fiber cloth; 4) placing the CMC / UiO66-NH2 synergistically modified carbon fiber obtained in step 3) in a MnO2 solution for a secondary solvothermal reaction, and after the reaction is completed, washing and secondary freeze-drying are performed to obtain a CMC / UiO66-NH2 / MnO2 synergistically non-destructive modified carbon fiber cloth; 5) The CMC / UiO66-NH2 / MnO2 synergistically non-destructive modified carbon fiber cloth obtained in step 4) is vacuum impregnated in a phenolic resin ethanol solution, dried, and then hot-pressed to obtain a CMC / UiO66-NH2 / MnO2 synergistically non-destructive modified carbon cloth reinforced resin friction material.
2. The method for preparing the CMC / UiO66-NH2 / MnO2 synergistically non-destructive modified carbon cloth reinforced resin friction material according to claim 1, characterized in that: In step 1), the carbon fiber cloth is soaked in acetone for 30-60 hours; the carboxymethyl cellulose solution is prepared by adding 0.6-1.2g of carboxymethyl cellulose to every 600g of deionized water; the soaking condition in the carboxymethyl cellulose solution is: soaking at 75-95°C for 2-4 hours.
3. The method for preparing the CMC / UiO66-NH2 / MnO2 synergistically non-destructive modified carbon cloth reinforced resin friction material according to claim 1, characterized in that: The dosage ratio of the pretreated carbon fiber cloth, diaminoterephthalic acid, N,N-dimethylformamide, zirconium chloride and acetic acid is (4-8) g: (0.108-0.216) g: (50-100) ml: (0.14-0.28) g: (2-10) ml; In step 2), the rotating speed of the mixing and stirring is 600-1500 r / min.
4. The method for preparing the CMC / UiO66-NH2 / MnO2 synergistically non-destructive modified carbon cloth reinforced resin friction material according to claim 1, characterized in that: In step 3), the temperature of the primary solvent thermal reaction is 100-140° C. and the time is 20-30 hours.
5. The method for preparing the CMC / UiO66-NH2 / MnO2 synergistically non-destructive modified carbon cloth reinforced resin friction material according to claim 1, characterized in that: In step 4), the MnO2 solution is prepared by adding 0.0316-0.0632 g of MnO2 to every 50-100 ml of deionized water.
6. The method for preparing the CMC / UiO66-NH2 / MnO2 synergistically non-destructive modified carbon cloth reinforced resin friction material according to claim 1, characterized in that: In step 4), the temperature of the secondary solvent thermal reaction is 100-140° C. and the time is 10-24 hours.
7. The method for preparing the CMC / UiO66-NH2 / MnO2 synergistically non-destructive modified carbon cloth reinforced resin friction material according to claim 1, characterized in that: In step 5), the mass fraction of the phenolic resin ethanol solution is 20%-25%; the immersion pressure is 0.07-0.1 MPa, and the immersion time is 24-26 hours.
8. The method for preparing the CMC / UiO66-NH2 / MnO2 synergistically non-destructive modified carbon cloth reinforced resin friction material according to claim 1, characterized in that: In step 5), the temperature of the hot pressing curing is 160-180° C., the pressure is 3-8 MPa, and the curing time is 6-12 min.
9. A CMC / UiO66-NH2 / MnO2 synergistically non-destructive modified carbon cloth reinforced resin friction material, characterized in that: The CMC / UiO66-NH2 / MnO2 synergistic non-destructive modified carbon cloth reinforced resin friction material is prepared by the preparation method of any one of claims 1 to 8, wherein the CMC / UiO66-NH2 / MnO2 synergistic non-destructive modified carbon cloth reinforced resin friction material has a tensile strength of 463.73-585.07 MPa; a friction coefficient of 0.124-0.134; and a wear rate of 3.69×10 -12 -7.24×10 -12 m 3 / (N·m).
10. Application of the CMC / UiO66-NH2 / MnO2 synergistic non-destructive modified carbon cloth reinforced resin friction material obtained by the preparation method of the CMC / UiO66-NH2 / MnO2 synergistic non-destructive modified carbon cloth reinforced resin friction material according to any one of claims 1 to 8 in vehicle braking.
Citation Information
Patent Citations
Modified carbon fiber with composite mechanical interlocking structure interface and composite material thereof
CN111676698A
UiO-66-(COOH) 2 / dopamine synergistically modified carbon fiber reinforced paper-based friction material and preparation method thereof
CN114016326A
Surface-modified carbon fiber, modification method and epoxy composite material thereof
CN116641227A
UiO66-NH2 modified carbon cloth reinforced resin-based friction material as well as preparation method and application thereof
CN118667293A